Benefits of bilingualism in the sphere of education - Zhetpisbayeva, B.A.; Stanciu, N.; Eskazinova, Zh.A. (Publ.KarSU, 2017)
The article examines the effective part of the phenomenon of bilingualism in the education system of the Republic of Kazakhstan with an emphasis on the specifics of the parallel learning of English and Kazakh languages. In addition the analysis of scientific pedagogical literature in linguistics, philosophy and pedagogy, psycholinguistics, social linguistics. The study identifies the main trends, types and aspects of multilingual education. In this article emphasizes the role of bilingualism in the field of intercultural communication, as well as in everyday life. The authors made appropriate conclusions regarding native ethnolingual in formation of secondary language personality. Researchers indicated the importance of a language of international communication together with knowledge of native language, contributing to the growth of the state's image in the international arena. The authors pointed out that research shows the importance of the development of the main types of speech activity: listening, speaking, reading, writing within the framework of bilingual education.
Білім беру саласындағы қостілділіктің тиімді жақтары
Эффективные стороны двуязычия в системе образования
Keywords: Language; bilingualism; personal; cognitive; academic; societal; situation; learning; culture; education